Acupuncture as an adjunctive therapy on embryo transfer day: a systematic review and meta-analysis of clinical pregnancy and live birth outcomes - Wang, Yixin; Ji, Jing; Duan, Na; Yin, Yanyun (Frontiers in Reproductive Health, 2025)
BackgroundAcupuncture is frequently employed during the process of embryo transfer. Nevertheless, its precise function in enhancing the likelihood of successful clinical pregnancy or live birth remains ambiguous.ObjectiveTo evaluate the efficacy of acupuncture as a complementary intervention to embryo transfer in managing female subfertility, compare the effects of acupuncture vs. sham acupuncture on clinical pregnancy rate in assisted reproductive technology, and clarify the optimal timing of acupuncture administration within in vitro fertilization protocols.MethodsAll literatures which described randomized controlled trials of acupuncture during the process of embryo transfer were obtained through searches of Cochrane Central, PubMed and Embase database (all to May 2025). Eleven randomized controlled trials were incorporated into the review. Selection of studies, quality assessment and data extraction were carried out independently by two review authors. Meta analysis was conducted, incorporating both risk ratios and 95% confidence intervals. The primary outcome measure was the clinical pregnancy rate, defined as the proportion of patients with an intrauterine gestational sac confirmed by ultrasound with or without a fetal heart. The secondary outcome measure was the live birth rate, defined as the proportion of patients with a pregnancy lasting ≥20 weeks or a birth weight of at least 400 g.ResultsEleven studies were selected for review, and nine of these were deemed acceptable based on their discussion of clinical pregnancy rate. By combining the studies and analyzing the results, it was concluded that acupuncture has demonstrated a positive impact on clinical pregnancy rate in contrast with the blank control group [1.25 (1.05–1.50), P = 0.013]. A statistical analysis revealed no significant differences between the sham acupuncture group and the acupuncture group [1.01(0.87–1.17), P = 0.907]. No statistically significant discrepancy between the Pulus Protocol [1.083(0.946–1.240)] and Delphi Consensus [1.164(0.938–1.445)]. Acupuncture has no positive impact on live birth rate during embryo transfer [1.01(0.88–1.15), P = 0.930]).ConclusionsThe results of this meta-analysis suggest that a positive correlation has been demonstrated between acupuncture and clinical pregnancy rate during embryo transfer when compared to the blank control group; however, this advantage does not hold when compared to the use of sham acupuncture. The Delphi Consensus revealed no discrepancy in clinical pregnancy rate when compared with the Pulus Protocol. It should be noted that the impact of acupuncture on live birth rate remains to be elucidated.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251067805, identifier (CRD420251067805).